Comparison of stress patterns and displacement in conventional cantilever fixed partial denture with resin bonded cantilever fixed partial denture: A finite element analysis - Prashanti E; Sajjan S; Kumar M (Wolters Kluwer Medknow Publications, 2010)
Aim: This study aims to analyze the stress patterns and displacement in the cantilever resin bonded fixed partial denture (RBFPD) and compare it with the conventional cantilever fixed partial denture using 3-D finite element analysis. Also, the effect of cement on the displacement and stress patterns in conventional cantilever fixed partial denture was to be analyzed. Materials and Methods: Three-dimensional models were prepared layer wise to depict the conventional cantilever and the cantilever RBFPD. Once the models were made, the material properties were assigned and divided into three groups. (2-conventional cantilever with resin cement, 1- conventional cantilever with GIC cement and 3-resin bonded cantilever with resin cement). Load was applied in vertical as well as lateral directions and the stress patterns along with displacement were analyzed. Results: The results revealed that the von Mises stresses in all the three groups were found to be almost equal under vertical loading. Under lateral loading, the stress was more in cantilever RBFPD. Displacement in all the three axes was significantly less in the cantilever RBFPD. Conclusion: Stress concentration in the lateral direction in cantilever RBFPD was found to be higher than the cantilever conventional group. Displacement in X, Y and Z axes was less in cantilever RBFPD.